Futures thinking becomes a priority for all globalized societies - Roland Benedikter (Discover Global Society)
Abstract This essay provides a concise impression of the many contemporary attempts to revitalize futures thinking. Futures thinking—in the sense of a systematic anticipatory approach based on sound scientific expertise and backed by socio-philosophical reasoning which must carefully balance idealism and pragmatism—was asleep for some time but is now rapidly becoming a top priority for all societies, independent of their socio-political system, composition, organization and outlook. Vis-a-vis recent global crises events and resulting “global” settings of combined uncertainty and acceleration, the trend goes towards a more meta-systemic and trans-sectoral “futures pan-humanism” in the sense of a “futures research science” conceived as a practically applicable tool of analysis of “futures in the present” featuring an inter- and trans-disciplinary character. This trend is what current trajectories in the global futures discourse exemplify, such as manifest at the Dubai Future Forums 2022, 2023 and 2024, as well as in other initiatives which aim, in widely converging ways, at showcasing, "casting" and “designing” creative interfaces of co-evolving futures. This text presents the most central buzz words, framings, concepts and overall style prevalent in contemporary global future fora and initiatives, taking them as symptomatic for an ongoing renaissance of approaches towards “futuring” in the advanced forms of “futures staging”, “futures casting” and “futures design” which, if this trend continues, could eventually lead to a more stable, post-conventional and wide-spread trans-national implementation of the discipline of “critical futures studies” in academia, policy and practice.